(untitled) (LEARNing Landscapes, 2014)
Questions of diversity and inclusion are central to learning to engage in narrative inquiry. By engaging in autobiographical narrative inquiry (Clandinin & Caine, 2012; Clandinin & Connelly, 2000), we tell and retell stories related to diversity. In doing so, we puzzle about inquiring in ethical ways alongside diverse participants. We tell and retell three stories in our efforts to break with the taken-for-granted in our lives. We draw forward resonances around the challenging, yet ethical necessity, of facing ourselves (Anzaldua, 1987/1999; Lindemann Nelson, 1995) as we attend to the complexity of lives.